1998
DOI: 10.1016/s0022-5347(01)63712-1
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopic Endopyelotomy at a Single Setting

Abstract: Ureteroscopic endopyelotomy without preoperative stenting is effective and safe for ureteropelvic junction obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…Therefore, blood supply to the surrounding heated tissue may be damaged. The second advantage of laser is the small diameter and flexibility of laser fibers that enables its passage through small-diameter semirigid and flexible ureteroscopes [5,10].…”
Section: Ureteroscopic Laser Endopyelotomymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, blood supply to the surrounding heated tissue may be damaged. The second advantage of laser is the small diameter and flexibility of laser fibers that enables its passage through small-diameter semirigid and flexible ureteroscopes [5,10].…”
Section: Ureteroscopic Laser Endopyelotomymentioning
confidence: 99%
“…The complications of ureteroscopic endopyelotomy had decreased dramatically in recent series, and they were usually minor in comparison with earlier series [5,40]. The reasons include the improvement of ureteroscopic instruments, such as development of smaller semirigid and flexible ureteroscopes with improved visibility, the utilization of laser energy, increasing experience with the procedure, and exclusion of patients with crossing vessels [21•].…”
Section: Complications Of Ureteroscopic Laser Endopyelotomymentioning
confidence: 99%
See 1 more Smart Citation
“…The indications and contraindications for this approach are the same for other endourologic approaches, except that a retrograde approach is not recommended in the setting of upper-tract stones. Success rates exceeding 80% are achieved with follow-up as long as 4 years [73,[83][84][85]. Unfortunately, recent studies have shown that with longer follow-up, the success of this approach deteriorates to approximately 65% to 78%, with many patients requiring subsequent procedures to treat recurrence of obstruction [86,87].…”
Section: Endourologic Managementmentioning
confidence: 99%
“…2), a 3F electrocautery probe, or a Holmium laser fiber (Fig. 3), with equally satisfactory outcome (75% to 85% success rate) [34][35][36][37].…”
Section: Retrograde Techniquesmentioning
confidence: 99%